Military burden determinants in Southern Africa, 1996-2005: a cross-section and panel data analysis: paper presented at Economic Development in Africa Conference, held at St Catherineís College - Tambudzai, Zachary (2016)
A few studies have focused on the determinants of military expenditure in Africa in general and southern Africa in particular. Most of the studies are not exclusively on this region but cover developing countries in general, with a few countries from southern Africa. Those that have focused on southern Africa are longitudinal case studies rather than cross-sectional. For instance, Batchelor etal (2002), for South Africa and Tambudzai (2006), for Zimbabwe. This article tries to fill this gap in the literature by econometrically testing for the factors that affect military expenditure in southern Africa, utilizing cross-section and pooled data estimations methods. The findings of this study confirm the importance of both economic and strategic variables in the determination of the level of military expenditure in developing countries. The strategic variables, however, have greater influence on military burden in southern Africa.